All hands on deck: negotiation over gesture forms in collaborative discourse - Harrison, Simon; Adolphs, Svenja; Gillon Dowens, Margaret; Du, Ping; Littlemore, Jeannette (Elsevier, 2018)
Language Related Episodes occur when speakers explicitly question lexical and grammatical aspects of the language they are using, resulting in collaborative discourse and assisted performance from peers. This paper demonstrates how such negotiation and repair may occur in relation to the gestural component of a speaker's expression, leading us to introduce the parallel term ‘Gesture Related Episodes’. Our single case analysis reveals a range of issues that have received little attention, including the problems that people experience with gestures, what constitutes struggling in the gestural modality, and how people help each other to gesture more effectively in collaborative discourse. Our discussion links these issues to the L2 concerns and knowledge asymmetries in our data, as well as to conceptual and conventional features of gestures more generally.